Analisis CFD unjuk kerja kolektor photovoltaic/thermal berdasarkan metode pendinginan permukaan atas dan bawah - Nalis, Amrizal; Nugraha, Yulian; Irsyad, Muhammad; Yonanda, Ahmad; Setiawan, Ahmad Adi (Jurnal Rekayasa Proses, 2025)
This research analyses the effect of radiation and fluid mass flow rate variations on the thermal performance of Photovoltaic/Thermal (PV/T) collectors based on top-surface cooling and bottom-surface cooling methods. This research uses the ANSYS Fluent simulation method based on radiation variations of 500 W/m2, 750 W/m2, 1000 W/m2, 1250 W/m2 and fluid mass flow rates of 0.02 kg/s, 0.04 kg/s, 0.06 kg/s. The research results show that cooling the top surface is proven to be more effective than cooling the bottom surface. The highest temperature difference between top and bottom cooling for PV surface temperature is 2.64 oC at a mass flow rate of 0.04 kg/s and radiation of 1250 W/m2, meanwhile, the difference in average working fluid temperature is lower than 1 oC. For a three-fold increase in fluid flow rate from 0.02 kg/s to 0.06 kg/s, the respective temperature decrease for the PV surface and working fluid is 7% and 14% respectively for both types of working fluid flow.